2023
DOI: 10.3389/fnagi.2023.1035376
|View full text |Cite
|
Sign up to set email alerts
|

Effect and mechanism of acupuncture on Alzheimer’s disease: A review

Abstract: With the development trend of an aging society, Alzheimer’s disease (AD) has become an urgent problem in the field of medicine worldwide. Cognitive impairment in AD patients leads to a decline in the ability to perform daily living and abnormalities in behavior and personality, causing abnormal psychiatric symptoms, which seriously affect the daily life of patients. Currently, mainly drug therapy is used for AD patients in the clinic, but a large proportion of patients will experience drug efficacy not working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…The current body of reviews indicated that the combination of acupuncture and medicine yielded more benefits for people with AD in comparison to the use of medication alone [ 15, 23–28 ]. In the realm of animal experimentation, numerous research had been conducted to investigate the presence of acupuncture intervention in AD through diverse mechanisms [ 29 ], including to alterations in synaptic morphology and structure by regulation of some relevance protein expression [ 30, 31 ], mitigation of Aβ deposition [ 32, 33 ] and excessive tau protein phosphorylation [ 34–37 ], inhibition of central nervous system inflammation and neuronal apoptosis [ 38–40 ], and resistance against oxidative stress [ 41, 42 ]. Acupuncture is an intervention based on acupoints, and multiple literature studies on the selection of acupoints for AD acupuncture intervention have found that ST36 ( Zusanli ) and CV12 ( Zhongwan ) acupoints were one of the more commonly used acupoints in AD acupuncture intervention [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current body of reviews indicated that the combination of acupuncture and medicine yielded more benefits for people with AD in comparison to the use of medication alone [ 15, 23–28 ]. In the realm of animal experimentation, numerous research had been conducted to investigate the presence of acupuncture intervention in AD through diverse mechanisms [ 29 ], including to alterations in synaptic morphology and structure by regulation of some relevance protein expression [ 30, 31 ], mitigation of Aβ deposition [ 32, 33 ] and excessive tau protein phosphorylation [ 34–37 ], inhibition of central nervous system inflammation and neuronal apoptosis [ 38–40 ], and resistance against oxidative stress [ 41, 42 ]. Acupuncture is an intervention based on acupoints, and multiple literature studies on the selection of acupoints for AD acupuncture intervention have found that ST36 ( Zusanli ) and CV12 ( Zhongwan ) acupoints were one of the more commonly used acupoints in AD acupuncture intervention [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although ACU interventions have not been extensively studied in meta-analyses of acupuncture, there is growing evidence supporting their cognitive improvement effects. ACU intervention at the acupoints “Baihui,” “Dazhui,” “Shenshu,” and “Zusanli” improved cognitive function, especially learning and memory, by repairing synaptic damage in patients with cerebral ischemia, and exerted neuroprotective effects by modulating the expression of CREB , BDNF , BCL2 , and BAX genes 70 , 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have documented the benefits of acupuncture in the management of Alzheimer's disease. The mechanism of acupuncture in treating Alzheimer's disease involves several factors, such as regulating Aβ metabolism and tau protein phosphorylation in a beneficial way, modulating neurotransmitters, reducing damage to synaptic and neuronal function, suppressing neuroinflammatory responses, and enhancing brain energy metabolism (87)(88)(89). Thus, acupuncture intervention in Alzheimer's disease has a multi-target, multi-pathway network modulation impact, which aligns with the overall modulation properties of acupuncture.…”
Section: Cognitive Impairmentmentioning
confidence: 93%